Evaluasi Program Penanggulangan TB Paru - Karbito, Karbito; Purwaningsih, Dewi; Aliyanto, Warjidin; Muslim, Azhari; Fikri, Ahmad; Murwanto, Bambang (Universitas Malahayati Bandar Lampung, 2024)
Background : One of the diseases that is still a problem in Indonesia that is Tuberculosis or TB, especially pulmonary TB, because it is the second highest disease in the world. Therefore, the TB control program in Indonesia is directed at accelerating the elimination of TB by 2030, with a strategy to increase the case detection rate to at least 90%, the treatment success rate to at least 90% and the prevention rate to at least 80%. Meanwhile, the TB incidence rate in Indonesia in 2022 will be 354 per 100,000 population. The problem of controlling pulmonary TB in Bandar Lampung City in 2022 has not yet reached the performance target, namely only reaching 54.3% from 74%.Purpose : This research aims are to find out how the Pulmonary TB management program is at the Sukamaju Public Health Center, Bandar Lampung City.Methods : The design of this research is qualitative, with the method used being interviews, namely Focus Group Discussion (FGD) and in-depth interviews, with triangulation of methods, data and sources, such as observation, etc.Result : The results of the research show that the Pulmonary TB management program at the Sukamaju Community Health Center, Bandar Lampung City has been running well with case detection and cure rates reaching 96.0%, while the obstacles experienced are only few and do not hinder the implementation of the program, namely the logistics of the mantoux test materials and cartridge.Conclution : The implementation of the pulmonary TB control programs at the Sukamaju Community Health Center, Bandar Lampung City is going well, where the TB program indicators have reached the target. The success of this program is also supported by TB cadres whose performance is quite successful. Keywords: TB, program, management Latar Belakang : Salah satu penyakit yang amsih menjadi masalah di Indonesia adalah Tublerculosis atau TB khususnya TB Paru, karena menjadi penyakit tertinggi kedua didunia. Oleh sebab itu program penanggulangan TB di Indonesia diarahkan untuk mempercepat eliminasi TB Tahun 2030, dengan strategi peningkatan angka penemuan kasus mencapai minimal 90%, dan angka keberhasilan pengobatan (success rate) minimal 90% serta angka pencegahan mencapai minimal 80%. Sementara insiden rate TBC di Indonesia tahun 2022 sebesar 354 per 100.000 penduduk. Permasalahan penanggulangan TB Paru di Kota Bandar Lampung pada tahun 2022 tersebut belum mencapai target kinerja yaitu baru mencapai 54,3% dari 74%.Tujuan : Tujuan penelitian ini adalah untuk mengetahui bagaimana pengelolaan program TB Paru di Puskesmas Sukamaju, Kota Bandar LampungMetode : Desain penelitian ini bersifat kualitatif, dengan metode yang digunakan wawancara yaitu Diskusi Kelompok Terarah/DKT (Focus Group Discussion/FGD) dan wawancara mendalam (Indepth Interview), dengan trianggulasi metode, data maupun sumber, seperti observasi, dsb.Hasil : Hasil penelitian bahwa pengelolaan program TB Paru di Puskesmas Sukamaju Kota Bandar Lampung telah berjalan dengan baik dengan angka pencapaian penemuan kasus dan penyembuhan mencapai 96,0%, sedangkan hambatan yang dialami hanya sedikit dan tidak serta tidak menggambat pelaksanaan program, yaitu terhambatnya logistic bahan tes mantuk dan catrige.Kesrmpulan : Simpulan penelitian ini Pelaksanaan program penanggulangan TB paru di Puskesmas Sukamaju, Kota Bandar Lampung berjalan dengan baik, dimana indikator-inkator program TB tersebut telah mencapai target. Keberhasilan program tersebut juga didukung oleh para kader TB yang cukup berhasil kinerjanya.